Manganite Memristive Devices : Recent Progress and Emerging Opportunities - Schulman, Alejandro; Huhtinen, Hannu; Paturi, Petriina (Institute of Physics Publishing, 2025)
Manganite-based memristive devices have emerged as promising candidates for next-generation non-volatile memory and neuromorphic computing applications, owing to their unique resistive switching behavior and tunable electronic properties. This review explores recent innovations in manganite-based memristive devices, with a focus on materials engineering, device architectures, and fabrication techniques. We delve into the underlying mechanisms governing resistive switching in manganite thin films, elucidating the intricate interplay of oxygen vacancies, charge carriers, and structural modifications. This review underscores breakthroughs in harnessing manganite memristors for a range of applications, from high-density memory storage to neuromorphic computing platforms that mimic synaptic and neuronal functionalities. Additionally, we discuss the role of characterization techniques and the need for a unified benchmark for these devices. We provide insights into the challenges and opportunities associated with the co-integration of manganite-based memristive devices with more mature technologies, offering a roadmap for future research directions.